Dynamic Evolution of the Zinc-Nickel Battery Industry and Evidence from China - Xiangze Shi; Xiao Li; Zijian He; Hui Jiang (Discrete Dynamics in Nature and Society)
This paper analyzes the development prospects of zinc-nickel battery industry, further investigates the industry competition in existing markets by mathematical modeling, calculates the equilibrium price and profit of the oligarch competition by using the method of Stackelberg equilibrium and Nash equilibrium, and makes a comparison between them. Then, we study and model the case of renting and selling simultaneously. In addition, we also study the impact of futures prices on the zinc-nickel battery companies and carry out numerical simulation. At the end of this paper, we analyze the location of zinc-nickel battery enterprises and the industry development under the COVID-19 pandemic. The finding show that the reduction of raw material cost is of great help to the development of the zinc-nickel battery industry.